2016
DOI: 10.1117/1.jpe.6.022001
|View full text |Cite
|
Sign up to set email alerts
|

Pathways toward high-performance perovskite solar cells: review of recent advances in organo-metal halide perovskites for photovoltaic applications

Abstract: , "Pathways toward highperformance perovskite solar cells: review of recent advances in organo-metal halide perovskites for photovoltaic applications," J. Photon. Energy 6(2), 022001 (2016), doi: 10.1117/1.JPE.6.022001. Abstract. Organo-metal halide perovskite-based solar cells have been the focus of intense research over the past five years, and power conversion efficiencies have rapidly been improved from 3.8 to >21%. This article reviews major advances in perovskite solar cells that have contributed to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
130
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(151 citation statements)
references
References 174 publications
3
130
0
2
Order By: Relevance
“…However, these laboratory based fabrication methods for perovskite films are not well-matched with a low costing, roll to roll process that is typical for large scale manufacture. 18 A solution would be to develop a one-step spray coating approach, which has already been successfully exploited for a range of electronic devices such as light emitting diodes, 19 photo-detectors, 20 field effect transistors 21 and also photovoltaics. 22,23 However, challenges still exist to deploy spray coating for perovskite photovoltaics as for instance thin layers as required for optimal device performance are still difficult to achieve by spray.…”
Section: Introductionmentioning
confidence: 99%
“…However, these laboratory based fabrication methods for perovskite films are not well-matched with a low costing, roll to roll process that is typical for large scale manufacture. 18 A solution would be to develop a one-step spray coating approach, which has already been successfully exploited for a range of electronic devices such as light emitting diodes, 19 photo-detectors, 20 field effect transistors 21 and also photovoltaics. 22,23 However, challenges still exist to deploy spray coating for perovskite photovoltaics as for instance thin layers as required for optimal device performance are still difficult to achieve by spray.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that V OC could be improved to up to ≈1.3 V if the trap density was reduced to N t < 10 13 cm −3 . The fill factor (FF) has been reported to be in the range of 0.70–0.85 for efficient perovskite solar cells . However, most of them are still dependent on the voltage sweep direction because of J–V hysteresis.…”
Section: Photovoltaic Parameters Of Ch3nh3pbi3 Perovskite Solar Cellsmentioning
confidence: 98%
“…Perovskite solar cells evolved from the mesoscopic structure (Figure 6a) in which the halide perovskite semiconductors replaced the light harvesting dye [23,70,71]. Later, the liquid electrolyte was replaced with a solid-state hole conductor.…”
Section: Perovskite Solar Cell Device Architecturesmentioning
confidence: 99%
“…The n -i-p is also called as normal device structure and p-i-n structure is also called as inverted device structure. Simply, depending on the position of the ETM and HTM, the device structure varies [70,[72][73][74]. The details about the different electron and hole transporting layers are discussed in the forthcoming section.…”
Section: Perovskite Solar Cell Device Architecturesmentioning
confidence: 99%